Plant Diversity in Tanen Home Gardens, Kemuning, Ngargoyoso, Central Java, and Their Potential in Keris Culture - Ariyanto, Joko; Muzayyinah, Muzayyinah; Karyanto, Puguh; Rinanto, Yudhi; Nurmiyati, Nurmiyati; Saputra, Alanindra; Diharjo, Dewi; Chusnunia, Chusnunia (The Ethnobiological Society of Indonesia, 2024)
The study was conducted in the home garden of Tanen hamlet in Ngargoyoso, Karanganyar, Central Java, Indonesia, which is situated at an elevation of 772 meters above sea level. The existence of Sukuh Temple near Tanen with Keris reliefs shows Keris culture in this region since ancient times. This study aims to identify plant species in the Tanen home garden suitable for Keris culture and understand their potential roles in Keris culture. Sampling was carried out using the cruising method, following the village road. Data on the plants on-site were collected through surveys conducted in the home garden. The plant species were classified with the assistance of The Mountain Flora of Java and www.theplantlist.com. The plants found were determined to be related to the Keris culture. The data were qualitatively analyzed to determine the role of each plant species in Keris culture and quantitatively assessed using the species richness index. The home garden in Tanen comprises a variety of species, with a species richness of 26 belonging to 19 families. Herbs make up 38% of the plant habitus in Tanen's home garden, which also has shrubs (31%), trees (23%), and bushes (8%). The most commonly used plant organs are leaves (24%) and flowers (24%). The potency of plants in the Tanen home garden for Keris culture is: for the name of the plant called in the blade of the Keris; for warangka (sheath) and deder (hilt); for equipment in Keris making; for cleansing agents; for fragrances (fragrant agents); and offering (food ingredients, spices). The primary potential use of plants in Tanen's home garden is for offering.